Levodopa nanoencapsulation in nanostarch as anti-parkinsonian drugs candidate - Sardjono, Ratnaningsih Eko; Dhea, Salsabila; Gunawan, Ramdhan; Kadarohman, Asep; Budiman, Anwar; Vidia Afina, Nuraini; Erdiwansyah, .; Rizalman, Mamat; Fitri, Dara; Melati, Khairuddean (Scientific Publishers, 2023)
Parkinson's disease is caused by damage to the dopaminergic nerves in brain. Levodopa has been widely used to treat Parkinson's disease. The levodopa nano encapsulation aims to improve drug-delivery efficiency thereby increasing the concentration of released levodopa in the brain. This study aims to obtain the optimum conditions for levodopa nano encapsulation in nanostarch, the characteristics of levodopa–starch nanocapsules, encapsulation efficiency, and its drug-release capabilities. Levodopa nano encapsulation has been carried out by ultrasonication method. Characterization has been carried out by FTIR, SEM, and TEM. The encapsulation efficiency is measured through changes in levodopa concentrations using a UV-Vis spectrometer. The drug release profile has been measured at pH 1.2 and 7.4 for 5 hours. The optimum conditions for levodopa nano encapsulation in nanostarch have been obtained at a mass ratio of nanostarch, maltodextrin and levodopa of 1:3:1. The SEM and TEM characterization show that levodopa–starch nanocapsules have a spherical morphology with the particle size ranged from 17.77-49.43 nm. The FTIR characterization show the presence of new peaks for C=O stretch and N-H bend. The highest encapsulation efficiency has been obtained at 46.11%. Drug release capability has been obtained by 40.93% in pH 1.2 media and 48.28% in pH 7.4 media for 5 hours of released time.